Results of the dissection of ripened prosciutto (dry cured ham) obtained from Casertana pig autochthonous ancient genetic type (AAGT) - Gigante G.; Barone C.M.A.; Castellano N.; Inglese F.; Matassino D. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The study was carried out on 26 prosciutti (dry-cured hams) obtained from the Casertana pig, an AAGT mostly reared in Campania (Italy), with the aim to point out some possible differences due to the sex in linear size and weight parameters detected at the dissection in pera, falsa pera and gambo. The results showed, within the limits of the observation field, that the maximum thickness is higher in the females (P < 0.05), as well as the weight of pera (P < 0.05) and falsa pera (P < 0.05).
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)